2015
DOI: 10.3171/2014.9.peds14333
|View full text |Cite
|
Sign up to set email alerts
|

Flow diversion for complex intracranial aneurysms in young children

Abstract: Pediatric intracranial aneurysms are exceedingly rare and account for less than 5% of all intracranial aneurysms. Open surgery to treat such aneurysms has been shown to be more durable than endovascular techniques, and durability of treatment is particularly important in the pediatric population. Over the past 2 decades, however, a marked shift in aneurysm treatment from open surgery toward endovascular procedures has occurred for adults. The authors describe their early experience in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
34
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(34 citation statements)
references
References 16 publications
0
34
0
Order By: Relevance
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Reports in the literature, however, are conflicting concerning the optimal strategy in using this new device. 1,2,4,13,15,16,[18][19][20][21] The addition of coil embolization to flow diversion, while prevalent in daily use, has not been subjected to a large systematic analysis. [7][8][9][10][11]16,[21][22][23][24] The earliest case report hypothesized that coils within the aneurysm sac can augment the degree of flow diversion with the goal of improved occlusion of the aneurysm.…”
mentioning
confidence: 99%
“…[1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17] Reports in the literature, however, are conflicting concerning the optimal strategy in using this new device. 1,2,4,13,15,16,[18][19][20][21] The addition of coil embolization to flow diversion, while prevalent in daily use, has not been subjected to a large systematic analysis. [7][8][9][10][11]16,[21][22][23][24] The earliest case report hypothesized that coils within the aneurysm sac can augment the degree of flow diversion with the goal of improved occlusion of the aneurysm.…”
mentioning
confidence: 99%
“…However, there are few case reports on the use of flow diverters in the pediatric population. [2][3][4][5][6][7][8][9][10][11] In this retrospective study, we report our experience with of flow diverters in 5 children with intracranial aneurysms and 2 children with carotid cavernous fistulas (CCFs). Through a review of our patient data and the relevant literature, we also summarize the current antiplatelet regimens used for children undergoing cerebrovascular interventions involving the placement of stents and flow diverters.…”
mentioning
confidence: 99%
“…Analyzing the 35 cases reported in the literature in which there is a somewhat detailed description of the placement of cerebral vascular scaffolds in children, we found that antiplatelet administration for endovascular treatment was extremely variable (On-line Table 2). [2][3][4][5][6][7][8][9][10][11]25,[31][32][33][34][35][36][37][38][39][40][41][42][43] There are neither guidelines published on antiplatelet therapy (APT) in children with cerebrovascular diseases 25 nor conclusive trials on pediatric APT regimens. 44,45 Weight-based dose calculations extrapolated from an adult dosing of 75 mg per day are not only misleading but also may lead to lifethreatening consequences.…”
mentioning
confidence: 99%
“…12,15,17,29 As in adults, the treatment of intracranial aneurysms in children can involve microsurgical clip ligation, wrapping, and endovascular treatment including flow diversion, coiling, and embolization of the aneurysm and parent vessel. 1,13,14,20,30,34,37 The rate of new SAH is higher in both adults and children with a previous aneurysm rupture than in the general population; it occurs as a result of recurrent aneurysms as well as de novo aneurysm formation. 4,35,39 In pediatric patients with a mean follow-up of 4-6 years, 11,15,30 a 13%-23% cumulative rate of de novo aneurysm formation has been reported.…”
mentioning
confidence: 99%
“…1,13,14,20,30,34,37 The rate of new SAH is higher in both adults and children with a previous aneurysm rupture than in the general population; it occurs as a result of recurrent aneurysms as well as de novo aneurysm formation. 4,35,39 In pediatric patients with a mean follow-up of 4-6 years, 11,15,30 a 13%-23% cumulative rate of de novo aneurysm formation has been reported.…”
mentioning
confidence: 99%